Reduced Peripheral Skeletal Muscle Mass and Abnormal Reflex Physiology in Chronic Heart Failure - Piepoli, Massimo F.; Kaczmarek, Agnieszka; Francis, Darrel P.; Davies, L. Ceri; Rauchhaus, Mathias; Jankowska, Ewa A.; Anker, Stefan D.; Capucci, Alessandro; Banasiak, Waldemar; Ponikowski, Piotr (Circulation (New York, N.Y.), 2006)
Background— The muscle hypothesis implicates abnormalities in peripheral muscle as a source for the stimulus to the symptoms and reflex abnormalities seen in chronic heart failure (CHF). We investigated the relationship between skeletal muscle mass (with dual-energy x-ray absorptiometry) and activation of the ergoreflex (a peripheral reflex originating in skeletal muscle sensitive to products of muscle work) in CHF patients and whether this rapport is affected by the progression of the syndrome. Methods and Results— We assessed 107 consecutive CHF patients (mean age, 61.9±10.9 years; 95% male; 25 cachectics) and 24 age-matched normal subjects (mean age, 59.0±11.1 years; 91% male). Compared with normal subjects, patients had a higher ergoreflex (in ventilation, 6.2±.6.1 versus 0.6±0.6 L/min; P <0.0001) and a reduction in muscle mass (51.9±10.0 versus 60.3±8.8 kg; P <0.001). The ergoreflex was particularly overactive in cachectics ( P <0.05), accompanied by marked muscle mass depletion ( P <0.0005). In CHF, ergoreceptor hyperresponsiveness in both the arm and leg correlated with reduced muscle mass, abnormal indexes of exercise tolerance (peak V̇ o 2 , V̇ e /V̇ co 2 slope), ejection fraction, and NYHA functional class ( P <0.0001). In the cachectic population, the ventilatory response from ergoreflex to arm exercise was strongly inversely correlated with arm ( r =−0.65), leg ( r =−0.64), and total ( r =−0.61) lean tissues ( P <0.001 for all). Multivariate analysis showed that these relationships were independent of NYHA class, peak V̇ o 2 , and V̇ e /V̇ co 2 slope. Conclusions— Depleted peripheral muscle mass is associated with ergoreflex overactivity and exercise limitation in CHF, particularly in cachectic patients. The systemic activation of the muscle reflex system in CHF may reflect progression and deterioration of the clinical syndrome.